KAJIAN STRATEGIS KELITBANGAN BIDANG INFRASTRUKTUR DAN PENGEMBANGAN WILAYAH KOTA SEMARANG TAHUN 2021-2026 - Rukuh Setiadi; Reny Yesiana; Fadjar Hari Mardiansjah; Savira Nur Afifah Kusuma Putri (Jurnal Riptek, 2021)
Infrastructure development is very important in development of a city or region , like in Semarang City. It aims to improve possibilities and the ease in doing activities as  well as to overcome problems that occur to reach sustainable development. Research as input for evidence—based policy formulatin is one of the important steps to improve infrastructure and regional development . This study aims to strategically examine  infrastructure and regional development in Semarang City between 2021-2026. The results are composed in a roadmap for research, development, and policy evaluation activities for the institution in the Semarang City Government in the field of infrastructure and regional development that should be held in 2021-2026. The research used a mix method, which includes content analysis techniques, descriptive comparisons, gaps mapping, setting priorities, and roadmap formulation. The Final Draft of the RPJMD for the City of Semarang for 2021-2026 is the basic data of proposals and prioritis for the implementation of R&D activities. The main data analyzed are data on research, development, and evaluation activities that have been carried out by the city’s service institution in the field of infrastructure and regional development in 2016-2021. In addition, some proposed themes from the strategic study conducted in 2016 was also used as a consideration in formulating the proposed thematic activities. There are 35 proposed thematic activities  that are formulated, each proposal is given a direction on implementation priorities, directives for the person in charge, as well as for instructions for the form of implementation consisting of self-management and grants. The instruction of the proposed R&D theme is expecting to be a reference for regional institution in the field of infrastructure and regional development in carrying out R&D activities that can support the achievement of the vision and mission of the City of Semarang in 2021-2026.